Preparation of PMo12-modified MIL-101(Fe) composite material and its use in photocatalytic nitrogen fixation, and a method for improving the nitrogen reduction reaction efficiency of ammonia synthesis by photocatalytic nitrogen reduction reaction.

JP7943713B1Active Publication Date: 2026-10-30NINGXIA UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2026052611
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2025-06-03
Filing Date
2026-03-26
Publication Date
2026-10-30
Estimated Expiration
2046-03-26

Smart Images

  • Figure 0007943713000001_ABST
    Figure 0007943713000001_ABST
Patent Text Reader

Abstract

This invention relates to PMo 12 This invention provides the preparation of modified MIL-101(Fe) composite materials and their use in photocatalytic nitrogen fixation. [Solution] PMo 12 The method for preparing the modified MIL-101(Fe) composite material involves mixing an iron source, terephthalic acid, and Keggin-type POM, reacting them, and then PMo 12 The process includes obtaining a modified MIL-101(Fe) composite material, wherein the Kegging-type POM is H3PMo 12 O 40 This material uses MIL-101(Fe) as its main framework and Keggin-type POM as a functional guest, assembled and composited by solvothermal method. The introduction of POM solves problems such as light energy utilization rate and recombination of photogenerated carriers, thereby improving the photocatalytic nitrogen fixation effect. Furthermore, POM acts as an electron repeater, storing and transferring electrons, providing abundant electrons to activate inert N2, thereby producing the target product NH4. + This can improve the yield.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention belongs to the field of photocatalytic nitrogen reduction technology, and more specifically, PMo 12 This paper relates to the preparation of modified MIL-101(Fe) composite materials and their use in photocatalytic nitrogen fixation. [Background technology]

[0002] Ammonia (NH3) occupies an irreplaceable strategic position in agricultural production and industrial manufacturing as an important raw material for the chemical industry and a hydrogen energy carrier. Current industrial ammonia synthesis mainly relies on the Haber-Bosch process, which is realized through catalytic synthesis of N2 and H2 under high temperature and pressure conditions. While this technology enables large-scale production, it has significant drawbacks, such as high energy consumption and large amounts of carbon dioxide emissions. Such a production mode with high carbon emissions and high energy consumption runs counter to the concept of sustainable development, and therefore the development of new environmentally friendly ammonia synthesis technologies has become an important direction in the field of energy chemistry.

[0003] Photocatalytic nitrogen reduction reactions offer a new pathway for clean ammonia synthesis. This technology mimics the natural photosynthetic mechanism, utilizing inexhaustible solar energy to drive ammonia synthesis from N2 and H2O under ambient temperature and pressure conditions. However, overcoming significant energy barriers is necessary for the dissociation of strong covalent bonds in ammonia molecules, and the number of reaction-active sites is limited. Therefore, there is a strong need to develop novel photocatalysts with high carrier separation efficiency and excellent nitrogen activation capabilities.

[0004] Metal-organic frameworks (MOFs) are crystalline porous materials assembled from metal cluster nodes and organic ligands. Their periodically arranged metal cluster nodes possess abundant unoccupied d-orbital active sites, making them an ideal medium for linking N2 molecular binding sites with biomimetic designs of FeMo cofactors. This has attracted considerable attention in the study of artificial nitrogenase catalytic systems. However, while the organic ligands in MOFs generate photogenerated electrons through light-harvesting effects, and structural design allows for the realization of Fe protein-like electron transport pathways, the lack of structural units similar to P clusters leads to serious photogenerated electron-hole pair recombination, significantly limiting the catalytic efficiency of their photo-driven biomimetic nitrogen fixation. Therefore, the development of photocatalytic nitrogen fixation catalysts with high catalytic efficiency is crucial. [Overview of the project] [Problems that the invention aims to solve]

[0005] The object of the present invention is PMo 12 The objective is to provide the preparation of a modified MIL-101(Fe) composite material and its use in photocatalytic nitrogen fixation, thereby solving the problems present in the prior art and enabling the preparation of a photocatalytic nitrogen fixation catalyst with high catalytic efficiency. [Means for solving the problem]

[0006] To achieve the above objective, the present invention provides the following scheme.

[0007] One of the technical schemes of the present invention: PMo 12 This provides a method for preparing modified MIL-101(Fe) composite materials. The iron source, terephthalic acid, and Keggin-type POM are mixed and reacted, and the PMo 12 The step includes obtaining a modified MIL-101(Fe) composite material, The aforementioned Kegging-type POM is H3PMo 12 O 40 That is the case.

[0008] Preferably, the PMo 12The specific steps of the preparation method of the modified MIL-101(Fe) composite material are as follows: Dissolving an iron source in a solvent to obtain a mixed solution, mixing the mixed solution, terephthalic acid and Keggin-type POM, and allowing them to react, to obtain the PMo 12 modified MIL-101(Fe) composite material, wherein the Keggin-type POM is H3PMo 12 O 40 .

[0009] Preferably, the solvent includes one or more of N,N-dimethylformamide, ethanol and water.

[0010] Preferably, the iron source includes one or more of iron chloride, iron nitrate and iron sulfate.

[0011] Preferably, the ratio of the used amounts of the iron source, terephthalic acid and Keggin-type POM is 4~6mmol:1~2mmol:150~200mg.

[0012] Preferably, the reaction temperature is 100~120°C, and the time is 20~24 hours.

[0013] Preferably, after the reaction is completed, the method further includes the steps of washing and drying.

[0014] The second technical solution of the present invention: provides the PMo 12 modified MIL-101(Fe) composite material prepared by the above preparation method.

[0015] The third technical solution of the present invention: provides the use of the above PMo 12 modified MIL-101(Fe) composite material in the field of photocatalytic nitrogen fixation.

[0016] The fourth technical solution of the present invention: provides a method for improving the nitrogen reduction reaction efficiency of ammonia synthesis by a photocatalytic nitrogen reduction reaction, which comprises the step of performing ammonia synthesis by a photocatalytic nitrogen reduction reaction using the above PMo 12 modified MIL-101(Fe) composite material as a catalyst.

[0017] The technical mechanism of this invention is as follows.

[0018] Polymetallic oxoacids (POMs) are a type of transition metal polyoxoanion nanocluster with atomic-level precision. The supramolecular assemblies formed by their complexation with MOFs exhibit unique electron transfer properties. POMs function as "electron repeaters," enabling fast and reversible multi-electron transfer while maintaining structural cooperation with MOFs. This property effectively mimics the electron-regulating function of P clusters in nitrogenases. Simultaneously, the strong electronegativity of the POM polyacid clusters allows them to continuously attract electrons from the metal clusters of MOFs. This not only strengthens the d-orbitals of the metal nodes to adsorb N2 and promotes the excitation of more electrons, but also excites the directional transfer of occupied d-orbital electrons to N-Nπ* antibonding orbitals, thereby realizing an N2 activation mechanism similar to that of biological nitrogen-fixing enzymes.

[0019] This invention mimics an electron transfer / storage unit using Fe cluster nodes in MIL-101(Fe) and connects to a Kegging-type PMo via covalent bonding. 12 The core catalyst site and electron repeater are immobilized, forming a clear Fe-O-Mo interface. This design realizes a division of labor mechanism between the electron transport pathway and the active site, overcoming the significant challenge of carrier recombination in MOF-based materials. Based on the above synergistic effect, the MOF-POM composite system shows high similarity to nitrogenase in the mimicry of the electron transport pathway, the construction of the active site, and the biomimetic nature of the catalytic mechanism, providing an important theoretical foundation for the development of a biological nitrogen fixation catalyst platform.

[0020] The present invention of PMo 12 When applying modified MIL-101(Fe) composite materials to the field of photocatalytic nitrogen fixation, the photocatalytic nitrogen reduction reaction uses ultrapure water and N2 as raw materials, and the composite material PMo 12 @MIL-101(Fe) has high catalytic activity. MIL-101(Fe) and PMo 12Because they form a bridging structure (as shown in Figure 8), MIL-101(Fe) itself can expand its visible light absorption range. Furthermore, due to the bridging structure, photogenerated electrons on MIL-101(Fe) are PMo 12 PMo 12 By recombining with the holes above, the introduction of POM can solve problems such as light energy utilization rate and recombination of photogenerated carriers, thereby improving the photocatalytic nitrogen fixation effect.

[0021] Terephthalic acid, as a ligand, plays a role in adjusting the pore size of the MOF and is irreplaceable. If it is replaced with another ligand, the cross-linking structure of the present invention cannot be formed. PMo specified in the present invention 12 The preparation parameters of the modified MIL-101(Fe) composite material significantly affect the formation of bridged structures. While bridged structures can be formed within the range of preparation parameters specified in this invention, exceeding the range of preparation parameters limited in this invention results in the formation of other structures (e.g., isolated dispersed structures due to physical mixing of POM / MOF, structures in which POM is confined within MOF pores, or heterogeneous mixed structures of POM aggregates and MOF). As a result, bridged structures cannot be formed, leading to a significant decrease in the photocatalytic nitrogen fixation effect. [Effects of the Invention]

[0022] This invention discloses the following technical effects.

[0023] This invention is based on the design concept of nitrogenase biomimetic photocatalysts, using MIL-101(Fe) as the main framework and Keggin-type POM as the functional guest. Using the solvothermal method, POM is covalently bonded to the support MIL-101(Fe) and composited, which is then applied to ammonia synthesis via photocatalytic nitrogen reduction. This synthesis process does not require high equipment, produces little pollution, and can be easily implemented under room temperature conditions.

[0024] The photocatalytic nitrogen reduction reaction uses ultrapure water and N2 as raw materials, and composite material PMo 12 @MIL-101(Fe) has high catalytic activity. MIL-101(Fe) and PMo12 Because it forms a bridging structure, MIL-101(Fe) itself can expand its visible light absorption range, and furthermore, due to the bridging structure, photogenerated electrons on MIL-101(Fe) are PMo 12 PMo 12 By recombining with the holes above, the introduction of POM can solve problems such as light energy utilization rate and recombination of photogenerated carriers, thereby improving the photocatalytic nitrogen fixation effect. In addition, POM acts as an electron repeater, storing and transferring electrons, providing abundant electrons to activate inert N2, thereby producing the target product NH4. + To improve the yield. [Brief explanation of the drawing]

[0025] [Figure 1] These are the XRD patterns of MIL-101(Fe) and composite materials prepared in Examples 1-4. [Figure 2] These are the Fourier transform infrared spectra of MIL-101(Fe) and composite materials prepared in Examples 1-4. [Figure 3] This diagram shows the photocatalytic performance of MIL-101(Fe) and composite materials prepared in Examples 1-4. [Figure 4] This is a photocatalytic performance cycle diagram of the PMo12@MIL-101(Fe) composite material in Example 5. [Figure 5] This is the NMR spectrum of NH4+ generated in the reaction system of Example 6. [Figure 6] This is a diagram illustrating the photocatalytic oxygen generation performance of PMo12@MIL-101(Fe) in Example 7. [Figure 7] This diagram shows the photocatalytic performance of PMo12@MIL-101(Fe) under different conditions. [Figure 8] These are model diagrams of MIL-101(Fe) and PMo12@MIL-101(Fe), where (a) is MIL-101(Fe) and (b) and (c) are PMo12@MIL-101(Fe). [Modes for carrying out the invention]

[0026] Herein, various exemplary embodiments of the present invention will be described in detail, but this detailed description should not be interpreted as limiting the present invention, but rather as providing a more detailed description of specific aspects, characteristics, and embodiments of the present invention.

[0027] It should be understood that the terminology used in this invention is merely for the purpose of describing specific embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that the intermediate values ​​between the upper and lower limits of the range are also specifically disclosed. Any stated value or intermediate value within the stated range, as well as any smaller range between any other stated value or intermediate value within the said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included in or excluded from the range.

[0028] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art. While this invention describes only preferred methods and materials, any similar or equivalent methods and materials may be used in the practice or testing of this invention. All references used herein are incorporated by reference to disclose and describe methods and / or materials related to those references. In the event of any conflict between the incorporated references and the information herein, the information herein shall prevail.

[0029] Various improvements and modifications can be made to specific embodiments of the specification of the present invention without departing from the scope or spirit of the present invention, which will be apparent to those skilled in the art. Other embodiments derived from the specification of the present invention will also be apparent to those skilled in the art. The specification and examples of the present invention are merely illustrative.

[0030] As used herein, terms such as "include," "contain," "have," and "contain" are all open terms, meaning that "include" does not necessarily mean "not limited to these."

[0031] It should be noted that all aspects not described in detail in this invention are standard operating methods in the art and are not the focus of this invention.

[0032] Unless otherwise specified, the raw materials used in the following embodiments of the present invention are all commercially available products, and the origin of these commercially available products does not affect the technical effects of the present invention.

[0033] Unless otherwise specified, the room temperature in the present invention is 25±5℃.

[0034] Example 1

[0035] S1: Under room temperature conditions, FeCl3·6H2O (0.811 g, 5 mmol) was weighed out and dissolved in 60 mL of N,N-dimethylformamide (DMF). The mixture was sonicated until it was completely dissolved and a yellow solution was formed. Subsequently, terephthalic acid (0.249 g, 1.5 mmol) was added to the mixture and stirred continuously for 30 minutes.

[0036] S2: The mixed solution obtained in step S1 was transferred to a reaction vessel and held at 110°C for 24 hours. After the reaction was complete, it was cooled to room temperature, centrifuged at a rate of 8000 r / min, and the solid product was taken and washed three times alternately with acetone and anhydrous ethanol. Finally, it was dried in a vacuum dryer at 80°C for 12 hours.

[0037] S3: The powder obtained in step S2 was ground and stored in a sample tube. The prepared sample was named MIL-101(Fe).

[0038] Example 2

[0039] S1: Under room temperature conditions, FeCl3·6H2O (0.811 g, 5 mmol) was weighed out and dissolved in 60 mL of N,N-dimethylformamide (DMF). The solution was sonicated until it was completely dissolved and a yellow solution was formed. Subsequently, terephthalic acid (0.249 g, 1.5 mmol) and 200 mg of H3PMo were added.12 O 40 The above mixture was added and continuously stirred for 30 minutes.

[0040] S2: The mixed solution obtained in step S1 was transferred to a reaction vessel and held at 110°C for 24 hours. After the reaction was complete, it was cooled to room temperature, centrifuged at a rate of 8000 r / min, and the solid product was taken and washed three times alternately with acetone and anhydrous ethanol. Finally, it was dried in a vacuum dryer at 80°C for 12 hours.

[0041] S3: The powder obtained in step S2 was ground and stored in a sample tube. The prepared sample was then processed in PMo 12 I named it @MIL-101(Fe).

[0042] Example 3

[0043] S1: Under room temperature conditions, FeCl3·6H2O (0.811 g, 5 mmol) was weighed out and dissolved in 60 mL of N,N-dimethylformamide (DMF). Sonication was performed until complete dissolution and a yellow solution were formed. Subsequently, terephthalic acid (0.249 g, 1.5 mmol) and 200 mg of H3PW were added. 12 O 40 The above mixture was added and continuously stirred for 30 minutes.

[0044] S2: The mixed solution obtained in step S1 was transferred to a reaction vessel and held at 110°C for 24 hours. After the reaction was complete, it was cooled to room temperature, centrifuged at a rate of 8000 r / min, and the solid product was taken and washed three times alternately with acetone and anhydrous ethanol. Finally, it was dried in a vacuum dryer at 80°C for 12 hours.

[0045] S3: The powder obtained in step S2 was ground and stored in a sample tube. The prepared sample was then processed using PW. 12 I named it @MIL-101(Fe).

[0046] Example 4

[0047] S1: Under room temperature conditions, FeCl3·6H2O (0.811 g, 5 mmol) was weighed out and dissolved in 60 mL of N,N-dimethylformamide (DMF). The solution was sonicated until it was completely dissolved and a yellow solution was formed. Subsequently, terephthalic acid (0.249 g, 1.5 mmol) and 200 mg of H4SiW were added. 12 O 40 The above mixture was added and continuously stirred for 30 minutes.

[0048] S2: The mixed solution obtained in step S1 was transferred to a reaction vessel and held at 110°C for 24 hours. After the reaction was complete, it was cooled to room temperature, centrifuged at a rate of 8000 r / min, and the solid product was taken and washed three times alternately with acetone and anhydrous ethanol. Finally, it was dried in a vacuum dryer at 80°C for 12 hours.

[0049] S3: The powder obtained in step S2 was ground and stored in a sample tube. The prepared sample was then processed using SiW. 12 I named it @MIL-101(Fe).

[0050] MIL-101(Fe), PMo obtained in Examples 1-4 12 @MIL-101(Fe), PW 12 @MIL-101(Fe) and SiW 12 Structural analysis of @MIL-101(Fe) was performed using X-ray diffraction and Fourier transform infrared spectroscopy. The results are shown in Figures 1 and 2.

[0051] Figure 1 shows the XRD patterns of MIL-101(Fe) and composite materials prepared in Examples 1-4.

[0052] Figure 2 shows the Fourier transform infrared spectra of MIL-101(Fe) and composite materials prepared in Examples 1-4.

[0053] As can be seen in Figure 1, the composite material PMo 12 @MIL-101(Fe), SiW 12 @MIL-101(Fe) and PW 12The diffraction peak of @MIL-101(Fe) matches the crystal structure of MIL-101(Fe), and also the three types of POM(H3PMo 12 O 40 H3PW 12 O 40 H4SiW 12 O 40 No diffraction peaks were observed. This indicates that the addition of POM does not affect the crystal structure of MIL-101(Fe). The chemical bonding properties of the three composite materials were evaluated by FT-IR.

[0054] As shown in Figure 2, H3PMo 12 O 40 The characteristic absorption peak signals are 1065, 962, 872, and 787 cm⁻¹. -1 They are located at Mo=0, P-0, and Mo-O respectively. b -Mo and Mo-O c - Attributable to vibrational modes of Mo coupling. Similarly, H4SiW 12 O 40 For these, 979, 925, 880 and 784 cm -1 Typical absorption peaks appear at W=0, Si-0, and WO, respectively. b -W and WO c - Corresponds to the vibration modes of W coupling. H3PW 12 O 40 For these, 1085, 984, 892, and 807 cm -1 Characteristic absorption peak signals appear at W=0, P-0, and WO, respectively. b -W and WO c - Corresponds to the vibration modes of the W coupling. Carrier MIL-101(Fe) is 1597, 1505 and 1393 cm⁻¹. -1 Characteristic absorption peaks are observed, corresponding to the C=0 asymmetric vibration, benzene ring skeletal vibration, and C=0 symmetric vibration modes of terephthalic acid, respectively. In the three composite materials, the skeletal vibration signal of MIL-101(Fe) and the characteristic vibration bands of the POM molecule were detected simultaneously. This clearly indicates that both the POM molecule and MIL-101(Fe) maintained their original chemical structures during the synthesis process of the composite materials, and that no structural dissociation occurred.

[0055] Example 5

[0056] A 300W xenon lamp (PLS-SXE 300, Beijing Perfect Light Co., Ltd.) was used as the light source, and the reaction temperature for the photocatalytic reaction was maintained at 25°C. The photocatalysts MIL-101(Fe) and PMo prepared in Examples 1-4 were used. 12 @MIL-101(Fe), SiW 12 @MIL-101(Fe) and PW 12 30 mg of MIL-101(Fe) was weighed out and placed in a quartz reactor. 100 mL of ultrapure water was added, and the reactor was sonicated for 3 minutes to uniformly disperse the photocatalyst. Before irradiation, the suspension was stirred in the dark for 30 minutes while blowing in N2 to allow equilibrium to be reached in the N2 adsorption and desorption on the photocatalyst surface. Then, the reactor was irradiated with a xenon lamp, and N2 was continuously passed through at a gas flow rate of 80 mL / min. 5 mL of the reaction solution was taken at regular intervals, and the photocatalyst was removed by centrifugation. The ammonia concentration in the reaction solution was measured by ion chromatography. The results are shown in Figure 3.

[0057] Figure 3 shows the photocatalytic performance of MIL-101(Fe) and composite materials prepared in Examples 1-4.

[0058] As can be seen from Figure 3, the photocatalysts MIL-101(Fe) and PMo 12 @MIL-101(Fe), SiW 12 @MIL-101(Fe) and PW 12 The ammonia production rate of @MIL-101(Fe) is 8.75 μmol·g each. -1 cat ·h -1 50.29 μmol·g -1 cat ·h -1 , 36.33 μmol·g -1 cat ·h -1 and 20.72 μmol·g -1 cat ·h -1The difference in performance is mainly due to the fact that molybdenum-based heteropoly acids exhibit stronger adsorption and activation capabilities for nitrogen molecules compared to tungsten-based heteropoly acids. This increases the chemiadsorption strength of N2 molecules, promoting the dissociation of N≡N bonds, improving nitrogen reduction efficiency, and ultimately resulting in superior catalytic activity.

[0059] The optimal photocatalyst PMo obtained in Example 2 12 Using @MIL-101(Fe), six cycle tests were performed according to the test procedure of Example 5. The interval between each cycle test was 1 hour, and the results of the cycle tests are shown in Figure 4.

[0060] Figure 4 shows the PMo in Example 5. 12 This is a photocatalytic performance cycle diagram of the MIL-101(Fe) composite material.

[0061] As can be seen in Figure 4, PMo 12 The photocatalytic cycling performance of @MIL-101(Fe) is essentially maintained, further demonstrating that the photocatalyst has good stability.

[0062] Example 6

[0063] NH4 in photocatalytic nitrogen fixation reactions + To verify the origin of the nitrogen, a mechanism study was conducted using isotope labeling. The test design was as follows: A 300W xenon lamp (PLS-SXE 300, Beijing Perfect Light Co., Ltd.) was used as the light source, and the reaction temperature of the photocatalytic reaction was maintained at 25°C. The photocatalyst PMo prepared in Example 2 12 30 mg of @MIL-101(Fe) was weighed out and placed in a quartz reactor. 100 mL of ultrapure water was added, and the mixture was sonicated for 3 minutes to uniformly disperse the photocatalyst. Before irradiation, the suspension was stirred in the dark for 30 minutes while blowing in N2 to allow equilibrium to be reached in the N2 adsorption and desorption on the photocatalyst surface. The photocatalytic reaction system was purified to eliminate environmental nitrogen contamination through three vacuum-argon displacement cycles, resulting in a high-purity solution. 15 N2 or 14N₂ was introduced to atmospheric pressure. After the photocatalytic reaction was completed, 30 mL of the reaction solution was taken, filtered through a 0.22 μm aqueous filter, concentrated sulfuric acid was added to adjust the pH value to 2, and then the mixture was concentrated to 10 mL using a rotary evaporator. At the same time, 600 μL of the concentrated solution was transferred to a 5 mm NMR sample tube, 20 μL of D₂O (99.99%, Sigma-Aldrich) was added thereto as a lock reagent, and the mixture was mixed for 30 seconds. An analytical test was performed using an AVANCE NEO 500M nuclear magnetic resonance spectrometer. The results are shown in Figure 5.

[0064] Figure 5 shows NH₄ generated in the reaction system in Example 6 + 's 1 ¹H NMR spectrum diagram.

[0065] From Figure 5, a doublet with a coupling constant J=75 Hz for 15 NH₄ + can be observed, and at the same time, a triplet with a coupling constant J=53 Hz is assigned to 14 NH₄ + , which verifies that the NH₄ + in the reaction system is derived from N₂ molecules. This proves that the photocatalyst obtained in the present invention is applicable to ammonia synthesis via the photocatalytic nitrogen reduction reaction.

[0066] Example 7

[0067] The photocatalytic nitrogen fixation process (i.e., the process of ammonia synthesis via the photocatalytic nitrogen reduction reaction) is often accompanied by the generation of O₂. 30 mg of the photocatalyst PMo 12 @MIL-101(Fe) powder was dispersed in 100 mL of ultrapure water, placed in a photocatalytic reaction apparatus, purged with carrier gas, and illumination with a 300 W xenon lamp was started. The generated gas was monitored online using a gas chromatograph. A TCD thermal conductivity detector was used as the detector, and high-purity argon was used as the carrier gas. Illumination was performed for 3 hours, and the oxygen generation amount of the photocatalyst was detected using the gas chromatograph, with detection performed every 1 hour during this period. The results are shown in Figure 6.

[0068] Figure 6 shows the PMo12 This is a diagram of the photocatalytic oxygen generation performance of @MIL-101(Fe).

[0069] As can be seen from Figure 6, the detected O2 generation amount is 50.08 μmol·g -1 cat ·h -1 , while the ammonia yield under a nitrogen atmosphere is 61.44 μmol·g -1 cat ·h -1 . Theoretically, the ratio of NH4 in the entire photocatalytic nitrogen fixation reaction is 4 / 3 relative to O2, and the actual generation amounts of NH4 and O2 in the photocatalytic reaction are close to this ratio. This indicates that in the biomimetic photocatalyst PMo + / O2 is 4 / 3, and the generation amounts of NH4 in the actual photocatalytic reaction + and O2 are close to this ratio. This indicates that in the biomimetic photocatalyst PMo 12 @MIL-101(Fe), photogenerated electrons are generated to reduce N2 to NH4 + , and photogenerated holes oxidize H2O to O2 and H+. This also proves that the photocatalyst obtained in the present invention is applicable to ammonia synthesis via photocatalytic nitrogen reduction reaction.

[0070] Example 8

[0071] PMo 12 To verify the photocatalytic performance of @MIL-101(Fe) under different conditions, the following tests were conducted: the photocatalytic experimental system consists of a xenon lamp light source (300W), a quartz photoreactor, a constant-temperature circulation device, and a vacuum filtration device. The specific operations are as follows: the photocatalyst PMo 1230 mg of @MIL-101(Fe) powder was accurately weighed and mixed with 100 mL of ultrapure water in a quartz photoreactor. The photocatalyst was confirmed to be uniformly dispersed by ultrasonic dispersion for 5 minutes. For photocatalysis experiments in different atmospheric environments, the reaction system was aerated with specified gases (high-purity N2, high-purity Ar, and air) at a rate of 5 sccm for 30 minutes. A constant temperature circulation system was activated to maintain a constant temperature of 25°C, and the magnetic stirrer was set to 400 r / min. The xenon lamp power supply was adjusted to an operating current of 15 A, fixed at a vertical distance of 10 cm from the liquid surface, and irradiation was performed. After the reaction was complete, the solid-liquid phase was separated using a vacuum filtration device (equipped with a 0.22 μm aqueous filter), and the product was detected. For performance testing in a dark environment, the irradiation procedure was omitted, and the other steps were the same as above. The results are shown in Figure 7.

[0072] As can be seen in Figure 7, PMo 12 @MIL-101(Fe) is NH4 under dark conditions or in an argon atmosphere. + No generation of NH4 was detected, confirming that the material itself was not contaminated with nitrogen. In addition, in the high-purity N2 and air system, NH4 + The amount of NH4 produced shows a linear trend with increasing light exposure time, and within 3 hours + The cumulative production amounts were 177.11 μmol·g each. -1 cat ·h -1 and 150.89 μmol·g -1 cat ·h -1 The performance in nitrogen was higher than that in air. This indicates that the photocatalytic performance improves accordingly as the purity of nitrogen increases. It was also confirmed that the photocatalyst can fix nitrogen in air, and that other small gas molecules do not affect its performance.

[0073] Example 9

[0074] H3PMo 12 O 40 The amount of PMo used 12To verify the effect of @MIL-101(Fe) on photocatalytic performance, the following tests were conducted.

[0075] First, PMo 12 @MIL-101(Fe) was prepared: The preparation process was the same as in Example 2, but H3PMo 12 O 40 The dosages were adjusted to 250 mg and 100 mg, respectively. Other details were the same as in Example 2.

[0076] Next, H3PMo 12 O 40 PMo obtained with different usage amounts 12 The ammonia production rate of @MIL-101(Fe) was detected. The specific detection process was the same as in Example 5. The results are as follows: H3PMo 12 O 40 The ammonia production rates for doses of 250 mg and 100 mg are 20.36 μmol·g, respectively. -1 cat ·h -1 and 25.23 μmol·g -1 cat ·h -1 That was the case.

[0077] Each example in this specification is described in a progressive manner, with each example focusing on the differences from the other examples. Identical or similar parts between examples should be referenced to one another.

[0078] The above description of the disclosed embodiments will enable those skilled in the art to practice or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be practiced in other embodiments without departing from the spirit or scope of the invention. Accordingly, the present invention is not limited to these embodiments shown herein, and the broadest scope should be given that is consistent with the principles and novel features disclosed herein.

Claims

1. PMo for use in ammonia synthesis by photocatalytic nitrogen reduction reaction 12 A method for preparing a modified MIL-101 (Fe) composite material, The iron source, terephthalic acid, and Kegin-type POM are mixed and reacted, and the PMO 12 The step includes obtaining a modified MIL-101 (Fe) composite material, The aforementioned Keggin-type POM is H 3 PMo 12 O 40 And, The PMO is characterized in that the ratio of the iron source, terephthalic acid, and Kegin-type POM used is 4-6 mmol: 1-2 mmol: 150-200 mg. 12 Method for preparing modified MIL-101 (Fe) composite materials.

2. A preparation method according to claim 1, The iron source is dissolved in a solvent to obtain a mixture, and the mixture, terephthalic acid, and Kegin-type POM are mixed and reacted, and the PMO 12 The preparation method according to claim 1, characterized by comprising the step of obtaining a modified MIL-101 (Fe) composite material.

3. The preparation method according to claim 2, characterized in that the solvent comprises one or more of N,N-dimethylformamide, ethanol, and water.

4. The preparation method according to claim 1 or 2, characterized in that the iron source includes one or more of ferric chloride, ferric nitrate, and ferric sulfate.

5. The preparation method according to claim 1 or 2, characterized in that the temperature of the reaction is 100 to 120°C and the duration is 20 to 24 hours.

6. The preparation method according to claim 1 or 2, further comprising the steps of washing and drying after the completion of the reaction.

7. PMo prepared by the preparation method described in Claim 1 12 Use of modified MIL-101 (Fe) composite materials in the field of photocatalytic nitrogen fixation.

8. A method for improving the nitrogen reduction reaction efficiency of ammonia synthesis by photocatalytic nitrogen reduction reaction, A PMo prepared by the preparation method described in Claim 1 12 A method for improving the nitrogen reduction reaction efficiency of ammonia synthesis via photocatalytic nitrogen reduction reaction, characterized by comprising the step of performing ammonia synthesis via photocatalytic nitrogen reduction reaction using a modified MIL-101(Fe) composite material as a catalyst.

Citation Information

Patent Citations

  • Preparation method and application of bimetallic photocatalytic functional POM / MOFs

    CN104324754A

  • Polyoxometallate composite metal-organic framework material used for visible light photocatalytic water splitting for hydrogen production, and preparation method thereof

    CN106939083A

  • MOF-based cotton cloth immobilized polyacid catalytic material as well as preparation method and application thereof

    CN112517078A

  • Composite photocatalytic material for air purification and preparation method thereof

    CN119793535A

  • Porous catalyst matrix for removing toxins found in tobacco combustion products

    JP2014521351A